Development of Mobile Learning App Based on Islamic and Science Integration to Improve Student Learning Outcomes - Saiful Amin; Sumarmi Sumarmi; Ramadhani Lausi Mkumbachi; Hendri Prastiyono; Muhammad Aliman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The integration of Islamic and science in Mobile Learning App (MLA) is an innovative and flexible digital learning media to help students learn during pandemic. This study aimed 1) to develop of MLA integrated with Islamic and science, 2) to determine the effect of MLA integrated with Islamic and science on students learning outcomes. This study used the Gall, Gall, & Borg Research and Development (R&D) model. The product fitness has been tested by the expert validators in learning media, materials, linguistics, and integration of Islamic and science, and the product effectiveness has been tested on students. The result showed that: 1) the integration of Islamic and science in MLA was fit to be used in learning with effective category and 2) the integration of Islamic and science in MLA was effective to improve student's learning outcomes in hydrosphere topic. Suggestions for media users include the following: 1) use media in an area with a strong network or internet connection; 2) conduct an outdoor study using mobile learning media; and 3) provide knowledge about using media before the lesson begins.This research provides positive energy for students as a provision to become agents of change in the 21st century, especially in mobile learning app based on Islamic and science.Research development using technology in science and Islamic curriculum also support to improve learning outcomes. Keywords: Development Mobile Learning, Islamic & Science Integration, Learning Outcomes